From ancient to avant‐garde: a review of traditional and modern multimodal approaches to surgical anatomy education. Issue 3 (18th September 2017) - Hu, Minhao; Wattchow, David; de Fontgalland, Dayan
Abstract : The landscape of surgical anatomy education is progressively changing. Traditional methods, such as cadaveric dissection and didacticism are being increasingly phased out in undergraduate courses for multimodal approaches incorporating problem‐based learning, radiology and computer‐based simulations. Although effective at clinically contextualizing and integrating anatomical information, these approaches may be a poor substitute for fostering a grasp of foundational 'pure' anatomy. Dissection is ideal for this purpose and hence remains the cornerstone of anatomical education. However, novel methods and technological advancements continually give way to adjuncts such as cadaveric surgery, three‐dimensional printing, virtual simulation and live surgical streaming, which have demonstrated significant efficacy alone or alongside dissection. Therefore, although divergent paradigms of 'new versus old' approaches have engulfed and divided the community, educators should seek to integrate the ancient and avant‐garde to comprehensively satisfy all of the modern anatomy learner's educational needs.